ISSUES OF TEYL IN INDONESIAN AND WHAT PARENT CAN DO ABOUT IT - Nugrahenny T. Zacharias (Indonesian JELT, 2010)
In Indonesia preschools with English-only or bilingual approaches have increasingly established and gained popularity among parents and children.  To parents who favors TEYL, teaching English since early age is believed to be more effective as children’s brains are believed to absorb language easily. The mastery of English is also perceived to be a valuable investment for the child’s future. However, some people view TEYL in Indonesia with a more critical eye. This is especially because TEYL starts as early as two years old when the young learners’ mother tongue, Indonesian, has not been acquired fully. As a result, many are worried if the acquisition of English would sacrifice the acquisition and quality of Indonesian, the nation lingua franca. The purpose of this paper is to raise parent’s awareness on the issues underlying the teaching of English to young learners. It aims to critically examine studies on early multilingualism in countries where English is the first language and compare them with Indonesia’s condition where English remains a foreign language. The paper starts with the narrative of Ben, my 22 month-old son, and his unique linguistic repertoire to illustrate the uniqueness and individuality of the linguistic landscape each young learner brings into classroom. After a brief introduction sharing the story of Ben, I look more closely at the issues of teachingEnglish to young learners. The paper concludes by suggesting reflective parenting approach to address the pervasive practice of TEYL in Indonesia and pose a number of issues to consider when immersing one’s child in English. Keywords:   Teaching English to young learners, multilingualism, early childhood education, second language acquisition, mother tongue, English as a foreign language, national identities.